Kondisi sosial ekonomi dan budaya masyarakat sekitar kawasan konservasi: studi kasus di Pulau Gag, Raja Ampat, Papua Barat - Baharinawati W. Hastanti; R. Gatot Nugroho Triantoro (Jurnal Penelitian Kehutanan Wallacea, 2012)
This study was aim to know the social, economic and cultural communities on the island of Gag, a nickel mining sites in the Marine Wildlife of the Raja Ampat Islands. In last years the region enter into a conflict between the central government (Ministry of Forestry) and the local government supported by the community. The conflict occurred because of a lack of public understanding of conservation of natural resources and the presence of nickel mining was expected to improve the welfare of local communities. Lack of public understanding of conservation is influenced by socio-economic conditions and local culture is partly because of geographical isolation, low levels of education and the difficulty of economic development. These factors led to the economic motivation of nickel mining in the region hope was forwarded to the exclusion of ecological impacts would arise from the nickel mining project.